(UJI AKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK DAUN KELOR (Moringa oleifera) DAN DAUN JAMBU BIJI (Psidium guajava L) TERHADAP Escherichia coli - aurelia zahra; dian marlina; destik wulandari (Jurnal Farmasi Indonesia, 2025)
Moringa leaves (Moringa oleifera) and guava leaves (Psidium guajava L.) contain antibacterial compounds such as alkaloids, tanins, saponins, and flavonoids that effectively inhibit Escherichia coli bacteria. This study aims to determine the antibacterial activity of the combination of both extracts using dilution, diffusion, and paper tape methods with concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.1%, 1.5%, and 0.7%, ciprofloxacin as a positive control and 10% DMSO as a negative control. The results of the dilution test showed that a concentration of 12.5% ​​was able to kill Escherichia coli bacteria, the 1:2 combination diffusion test provided the largest inhibition zone, indicating optimal antibacterial effectiveness. and the paper tape test showed an additive pattern indicating that the two extracts supported each other in inhibiting the growth of these bacteria